Functional Mechanisms of Treg in the Context of HIV Infection and the Janus Face of Immune Suppression - López-Abente, Jacobo; Correa-Rocha, Rafael; Pion, Marjorie (Frontiers in Immunology, 2016)
Regulatory T cells (Treg) play an important role in infections, by modulating host immune responses and avoiding the over-reactive immunity that in the case of HIV infection leads to a marked erosion and deregulation of the entire immune system. Therefore, the suppressive function of Treg in HIV-infected patients is critical because of their implication on preventing the immune hyperactivation, even though it could also have a detrimental effect by suppressing HIV specific immune responses. In recent years, several studies have shown that HIV-1 can directly infect Treg, disturbing their phenotype and suppressive capacity via different mechanisms. These effects include Foxp3 and CD25 downregulation, and the impairment of suppressive capacity. This review describes the functional mechanisms of Treg to modulate immune activation during HIV infection, and how such control is no longer fine-tune orchestrated once Treg itself get infected. We will review the current knowledge about the HIV effects on the Treg cytokine expression, on pathways implying the participation of different ectoenzymes (i.e. CD39/CD73 axis), transcription factors (ICER), and lastly on cAMP, one of the keystones in Treg suppressive function. To define which are the HIV effects upon these regulatory mechanisms is not only crucial for the comprehension of immune deregulation in HIV-infected patients but also for the correct understanding of the role of Treg cells in HIV infection.